TYPOLOGICAL ANALYSIS OF CLOTHING TERMS IN ENGLISH AND UZBEK - Abdullayeva Umida Nigmatullayevna; Jurakulova Raykhon Kholboyevna (Journals Park Publishing, 2022)
The origin of the word typology is typos-means «type», logos- means «science». A typology generally consists of a set of descriptive names or "types", attached to thumbnail sketches of typical behaviour and/or attitudes for each group. Typologies might be based on some specific behaviour (weekend hobbyist cooks v everyday pragmatic cooks) or on response to the client's brand (young aspirers v sceptical rejectors). But they can go much further, claiming to categories far broader attitudes and lifestyles.
Keywords: clothes terms; typology; categories’